Roadkill hotspots and driver awareness for endemic herpetofauna conservation in Western Thailand - PAPHAWADEE DUANGTA; THANAPHAT KLUBCHUM; PIYATHIP PIYAPAN; CHUTAMAS SUKHONTAPATIPAK; WEERACHON SAWANGPROH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Duangta P, Klubchum T, Piyapan P, Sukhontapatipak C, Sawangproh W. 2025. Roadkill hotspots and driver awareness for endemic herpetofauna conservation in Western Thailand. Biodiversitas 26: 6025-6038. University campuses, dense mosaics of roads, buildings, and small habitat patches, are rarely assessed for Wildlife-Vehicle Collisions (WVCs) despite predictable internal traffic and proximity to biodiverse areas. We addressed this gap at Mahidol University Kanchanaburi Campus (MUKA), Thailand, using a year-long, twice-daily carcass survey across four routes, supplemented by community reports and a concurrent driver questionnaire. We documented 170 carcasses from 31 species, dominated by reptiles (109, 64%) and amphibians (55, 32%), with few mammals (4, 3%) and birds (2, 1%). Spatial analysis revealed significant variation in roadkill incidence across routes (Kruskal-Wallis, H: 22.94, df: 3, p<0.0000424), with Route B identified as the primary hotspot adjacent to ponds and forest edges. Chi-square tests detected no association in taxonomic composition with distance to water, time of day, or season, yet roadkill incidents clustered near water (?200 m), at night, and during the rainy season, indicating ecologically meaningful tendencies despite non-significant group-wise differences. The driver survey (n: 85) revealed a qualitative size-based bias, with greater caution toward larger mammals compared with small, less conspicuous herpetofauna. Notably, records included Thai endemics (Jarujinia bipedalis, Gekko nutaphandi), underscoring conservation urgency where even low absolute losses can affect micro-endemic populations. We propose targeted mitigation measures—night/monsoon speed management, frog/snake icon signage before pond-adjacent bends, pilot micro-culverts with drift fencing, and wildlife-sensitive lighting only where crash risk warrants—and recommend exploring an Other Effective Area-Based Conservation Measure (OECM) approach for the Route B corridor to develop a transferable model for biodiversity-sensitive campus roads. Integrating these measures into campus planning could position MUKA as a model for biodiversity-sensitive infrastructure in the tropics, directly benefiting evolutionarily distinct and micro-endemic species.